Incontinence Is an Independent Risk Factor for Total Hip and Knee Arthroplasty - Jacob S. Budin, BS; Timothy L. Waters, BA; Lacee K. Collins, BS; Matthew W. Cole, MD; Julianna E. Winter, MD; Bela P. Delvadia, BS; Michael C. Iloanya, MD; William F. Sherman, MD, MBA (Arthroplasty Today, 2024)
Background: Urinary incontinence has been linked to worse postoperative pain, decreased physical function, and reduced quality of life in patients following total joint arthroplasty. The purpose of this study was to analyze whether incontinence is associated with increased postoperative medical and joint complications following primary total hip arthroplasty (THA) and total knee arthroplasty (TKA). Methods: A retrospective cohort study was conducted using a national insurance database. Thirty-two thousand eight hundred eleven patients with incontinence who underwent primary THA were identified and matched 1:4 with 129,073 patients without incontinence. Ninety-one thousand nine hundred thirty-five patients with incontinence who underwent primary TKA were matched 1:4 with 367,285 patients without incontinence. Medical and joint complication rates at 90 days and 2 years, respectively, were then compared for patient cohorts using multivariable logistic regressions. Results: Patients who underwent primary THA with incontinence had statistically higher rates of dislocation, periprosthetic fracture, aseptic revisions, and overall joint complications compared to controls. Patients who underwent primary TKA with incontinence had higher rates of mechanical failure, aseptic revision, and all-cause revision compared to controls. Conclusions: This study demonstrated an association between patients with incontinence and higher rates of dislocation, periprosthetic fractures, aseptic revisions, and overall joint complications following primary THA compared to controls. Patients with incontinence experience higher rates of mechanical failure, aseptic revision, and all-cause revision following TKA compared to controls. As such, perioperative management of urinary incontinence may help mitigate the risk of postoperative complications.